Triglyceride-glucose index and non-culprit coronary plaque characteristics assessed by optical coherence tomography in patients following acute coronary syndrome: A cross-sectional study - Zhao, Zi-Wei; Liu, Chi; Zhao, Qi; Xu, Ying-Kai; Cheng, Yu-Jing; Sun, Tie-Nan; Zhou, Yu-Jie (Frontiers in Cardiovascular Medicine, 2022)
Background: Triglyceride-glucose (TyG) index, a novel surrogate marker of insulin resistance, has been demonstrated to be significantly associated with cardiovascular disease. It remains indistinct regarding the association between TyG index and non-culprit coronary plaque characteristics in patients following acute coronary syndrome (ACS). Methods: The present study retrospectively recruited patients who were diagnosed with ACS and underwent non-culprit optical coherence tomography (OCT) examination. The study population was divided into 2 groups based on the median of TyG index, which was calculated as Ln [fasting triglyceride (TG) (mg/dL) × fasting blood glucose (FBG) (mg/dL) / 2]. The non-culprit plaque characteristics were determined by interpreting OCT images in accordance with the standard of previous consensus. Results: 110 patients (54.8 ± 12.1 years, 24.5% female) with 284 non-culprit plaques were included in the current analysis. TyG index was closely associated with high-risk plaque characteristics. Elevated TyG index was consistent to be an independent indicator for thin-cap fibroatheroma (TCFA) [odds ratio (OR) for per 1-unit increase 4.940, 95% confidence interval (CI) 1.652-14.767, P = 0.004; OR for taking lower median as reference 2.747, 95% CI 1.234-7.994, P = 0.011] and ruptured plaque (OR for per 1-unit increase 7.065, 95% CI 1.910-26.133, P = 0.003; OR for taking lower median as reference 4.407, 95% CI 1.208-16.047, P = 0.025) in fully adjusted model. The predictive value of TyG index for TCFA and ruptured plaque was moderate-to-high, with the area under the receiver operating characteristic curve (AUC) of 0.754 and 0.699 respectively. The addition of TyG index into a baseline model exhibited an incremental effect on the predictive value for TCFA, manifested as an increased AUC (0.681, 95% CI 0.570-0.793 vs. 0.782, 95% CI 0.688-0.877, P = 0.042), and significant continuous net reclassification improvement (0.346, 95% CI 0.235-0.458, P < 0.001) and integrated discrimination improvement (0.221, 95% CI 0.017-0.425, P = 0.034). TyG index failed to play an incremental effect on predicting ruptured plaque. Conclusion: TyG index, which is simply calculated from fasting TG and FBG, can be served as an important and independent risk predictor for high-risk non-culprit coronary plaques in patients following ACS.